Cooling Media Variation in Welding Stations and Its Effects on Labor Productivity and Operator Requirements - Darmawan, Didit; Hamid, Abdul (Universitas Sultan Ageng Tirtayasa, 2026)
Cooling media variation in welding stations determines waiting time between cycles, directly affecting labor utilization, daily welding cycles, and operator requirements. Water provides shortest waiting time but risks metallurgical damage on hardenable steels. Compressed air offers safest cooling for critical materials but longest waiting time. Water mist allows adjustable cooling rates, balancing productivity and quality. Labor utilization ranges from 50 percent with air cooling to 90 percent with water cooling under optimal conditions. Daily cycles per operator vary inversely with waiting time. Operator count for fixed production targets increases proportionally with waiting time. Material thickness, welding position, base metal type, application method, operator skill, and production line integration moderate these relationships. Economic analysis must consider trade offs between additional labor costs and rework or failure costs.